Efficient extraction of an arbitrary subset of data from large three-dimension volumes by manipulating of physical position of data; Современные техника и технологии; Т. 2 - Reviakin A. V. (Автоматическое управление и системная инженерия, 2015)
Заглавие с титульного экрана